2016
DOI: 10.1074/jbc.m115.704395
|View full text |Cite
|
Sign up to set email alerts
|

A “Love” Dart Allohormone Identified in the Mucous Glands of Hermaphroditic Land Snails

Abstract: Animals have evolved many ways to enhance their own reproductive success. One bizarre sexual ritual is the "love" dart shooting of helicid snails, which has courted many theories regarding its precise function. Acting as a hypodermic needle, the dart transfers an allohormone that increases paternity success. Its precise physiological mechanism of action within the recipient snail is to close off the entrance to the sperm digestion organ via a contraction of the copulatory canal, thereby delaying the digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
0
22
0
2
Order By: Relevance
“…Nevertheless, besides these morphological traits, other types of adaptations will also be relevant to investigate. Physiologically, for example, dart mucus composition could be altered to make the paternity enhancing effect more effective (e.g., new manipulative proteins or modification of the existing ones; Eberhard, ; Stewart et al., ). Consequently, it will now be extremely interesting to test whether mucus quality changes according to the level of sperm competition and whether it affects fertilization success.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, besides these morphological traits, other types of adaptations will also be relevant to investigate. Physiologically, for example, dart mucus composition could be altered to make the paternity enhancing effect more effective (e.g., new manipulative proteins or modification of the existing ones; Eberhard, ; Stewart et al., ). Consequently, it will now be extremely interesting to test whether mucus quality changes according to the level of sperm competition and whether it affects fertilization success.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of whether or not a mucus component from other sources evokes a similar effect, this would only indicate that the active component is possibly also used in a different context than dart shooting—which is not unusual for accessory gland products (e.g., Yi and Gillott, ). The latter scenario is strengthened by the identification of the digitiform gland component that induces one of the muscular contractions in the spermatophore receiving organ: the active peptide turns out to resemble buccalin, a known modulator of which different forms are used to change muscle contractions in freshwater and marine molluscs (Stewart et al, ). This particular peptide was named love‐dart allohormone (LDA), and is found in both C. aspersum and Theba pisana , the two species investigated by Stewart et al ().…”
Section: Measuring Gender Expression and Sex Allocationmentioning
confidence: 99%
“…The latter scenario is strengthened by the identification of the digitiform gland component that induces one of the muscular contractions in the spermatophore receiving organ: the active peptide turns out to resemble buccalin, a known modulator of which different forms are used to change muscle contractions in freshwater and marine molluscs (Stewart et al, ). This particular peptide was named love‐dart allohormone (LDA), and is found in both C. aspersum and Theba pisana , the two species investigated by Stewart et al (). The latter agrees with recent work showing that the effects of dart mucus are evolutionarily conserved within a number of dart‐bearing species (Kimura et al, ; Lodi and Koene, ,).…”
Section: Measuring Gender Expression and Sex Allocationmentioning
confidence: 99%
“…The latter hypothesis could be corroborated by experimental studies (Chase, ). It has been shown that the dart transfers an allohormone produced by the glands of the dart apparatus, the glandulae mucosae, into the body of the recipient (Stewart, Wang, Koene, Storey, & Cummins, ). This allohormone inhibits the intake of the spermatophore into a digesting organ so that more sperm can reach the sperm‐storing organ and fertilize eggs.…”
Section: Introductionmentioning
confidence: 99%